2020
DOI: 10.3390/ijms21061923
|View full text |Cite
|
Sign up to set email alerts
|

New Arylethanolimidazole Derivatives as HO-1 Inhibitors with Cytotoxicity against MCF-7 Breast Cancer Cells

Abstract: In this paper, a novel series of imidazole-based heme oxygenase-1 (HO-1) inhibitors is reported. These compounds were obtained by modifications of previously described high potent and selective arylethanolimidazoles. In particular, simplification of the central linker and repositioning of the hydrophobic portion were carried out. Results indicate that a hydroxyl group in the central region is crucial for the potency as well as the spatial distribution of the hydrophobic portion. Docking studies revealed a simi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 45 publications
1
13
0
Order By: Relevance
“…Compound 2 , a possible metabolite of 3 showed even lower inhibitory activity towards HO-1 (104.6 ± 5.8 μM). These results were consistent with previous structure-activity relationship (SAR) studies performed on azole-based analogs 44 , 45 , stressing that changes at the ethanolic chain are detrimental to the HO-1 inhibitory activity. Although compound 3 displayed a lower inhibitory potency towards the HO-1 with respect to parent derivative 1 , this aspect does not represent an issue since hybrid 3 acts as a mutual prodrug by releasing the parent drugs (i.e.…”
Section: Resultssupporting
confidence: 92%
“…Compound 2 , a possible metabolite of 3 showed even lower inhibitory activity towards HO-1 (104.6 ± 5.8 μM). These results were consistent with previous structure-activity relationship (SAR) studies performed on azole-based analogs 44 , 45 , stressing that changes at the ethanolic chain are detrimental to the HO-1 inhibitory activity. Although compound 3 displayed a lower inhibitory potency towards the HO-1 with respect to parent derivative 1 , this aspect does not represent an issue since hybrid 3 acts as a mutual prodrug by releasing the parent drugs (i.e.…”
Section: Resultssupporting
confidence: 92%
“…Interestingly, these responses were completely blocked by pretreatment with brazilin, indicating that brazilin inhibits hemin-induced HO-1 expressions through inactivation of JNK/Nrf2 in MCF-7 cells. In cancer cells, elevation of HO-1 expression increased in various tumors [ 15 , 16 , 17 , 18 , 19 ] and hemin, an iron-containing porphyrin with chlorine, is available HO-1 inducer in various cell types including normal and cancer cells [ 47 , 48 ]. In this study, we observed hemin-induced increases of HO-1 expression in MCF-7 cells and brazilin is potent regulator through HO-1 expression.…”
Section: Discussionmentioning
confidence: 99%
“…These molecules are non porphyrin-based and non competitive water-soluble inhibitors of HO-1 and exhibit low or even no inhibitory action on NOS, sGC, and CYP [ 211 , 212 ]. The first reported was Azalanstat [ 213 ], but other molecules and novel azole-based compounds derived from the structural modification of Azalanstat have been recently discovered [ 214 , 215 ]. Imidazole-based compounds have shown potent antitumor activity in prostate and breast cancer cell lines [ 216 ]; in a preclinical model of hormone-refractory prostate cancer, the small molecule imidazole-derived OB-24 acts in synergism with the conventional chemotherapy drug Taxol, preventing tumor growth and formation of lymph node and lung metastasis [ 188 ].…”
Section: Ho-1 and Tumor Therapiesmentioning
confidence: 99%